Analisis Kinerja Maqashid Syariah pada Bank Syari’ah - Sri Mulyani (Program Studi Ekonomi Syariah Institut Agama Islam Sunan Kalijogo Malang, 2019)
The purpose of this study was to determine the performance of Islamic sharia maqashid on Islamic banks which included the first objective maqashid syariah to educate individuals, maqashid syariah the second objective of upholding justice and the third objective maqashid sharia safeguarding welfare. This type of research is quantitative research with a descriptive approach. The source of data in this study uses secondary data obtained through Islamic bank publication financial reports from the websites of each Islamic bank, the website of Bank Indonesia and the website of the Financial Services Authority (OJK). The findings in the study show that the first objective of Maqashid Shari'ah, namely individual education (Tahdhib al fard) on Islamic banks during the 2012-2016 period shows that the ratio of shari'ah bank education and training costs is still less than 5%, which means maqashid shari'ah performance in terms of educating individuals (tahdhib al-fard) it is still not optimal for Islamic banks. Maqashid Syari'ah, the second objective of enforcing justice (Iqamah al 'Adl) on Islamic banks during the 2012-2016 period shows that Islamic banks have optimally had excellent maqashid sharia performance as indicated by the percentage of interest free income from Sharia Commercial Banks. the average is 99%. Whereas Maqashidsyari'ah's third goal of maintaining the benefit (Jalb al Maslahah) of Islamic banks during the period 2012-2016 shows that Islamic banks have not optimally maintained benefits. This is seen from the small percentage of zakat ratio and bank's profit ratio which is less than 5%.